Customs House, Steamers, and the Entrepôt: Zanzibar Trade Infrastructure Circa 1830–1888 - Pawełczak, Marek (African Economic History, 2020)
Keywords: Commerce -- Zanzibar -- 19e siècle

The Ivory Trade and Political Power in Nineteenth-Century East Africa - Gooding, Philip (Animal Trade Histories in the Indian Ocean World, 2020)
This chapter analyses ivory consumption and trade in the context of shifting political power in nineteenth-century East Africa. It firstly describes how increased demand for ivory and ivory products in the wider Indian Ocean World, Europe, and North America contributed to a decline in ivory’s ownership, usage, and display in East Africa. It then examines the nature and construction of Omani and coastal East African communities in East Africa’s interior to show how political power became increasingly tied to access and control the ivory trade. In nineteenth-century East Africa, ivory was transformed from a product with significant symbolic capital to one whose history was increasingly shaped by capitalistic forces.
Keywords: Commerce -- Zanzibar -- 19e siècle